2021
DOI: 10.7759/cureus.16416
|View full text |Cite
|
Sign up to set email alerts
|

Near-Peer Tutor: A Solution For Quality Medical Education in Faculty Constraint Setting

Abstract: Near-peer mentoring is a formal relationship in which more qualified students guide immediate junior students. It is an innovative approach to increase students' engagement from varied backgrounds and cultures in the health profession. This systematic review and meta-analysis aimed to investigate and compare the effectiveness of near-peer tutoring and faculty/expert teaching in health science undergraduates on knowledge and skill outcome. The review question considered was "how effective is nearpeer tutor comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…Our study found no significant differences between students’ perceptions of their near-peer tutors and their staff tutors, either in terms of facilitation or behaviour. These findings are consistent with those of a recent systematic review and meta-analysis of 16 studies of various health professions [ 26 ], which reported no meaningful difference in knowledge or skill scores among near-peer and expert teaching groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found no significant differences between students’ perceptions of their near-peer tutors and their staff tutors, either in terms of facilitation or behaviour. These findings are consistent with those of a recent systematic review and meta-analysis of 16 studies of various health professions [ 26 ], which reported no meaningful difference in knowledge or skill scores among near-peer and expert teaching groups.…”
Section: Discussionsupporting
confidence: 92%
“…Also like ours, Khapre et al's [26] study found that students felt more comfortable with near-peer tutors because of the latter's ability to create more relaxing learning environments, which in turn allowed them to ask and answer questions more openly and without fear of criticism. However, our participants also mentioned that near-peer tutors were better than staff ones at understanding their frustrations and seeing things from their perspective, which also made discussion easier.…”
Section: Social Cognitive and Professional Congruencesupporting
confidence: 53%
“…Our findings on the need for comprehensive efforts to prepare students to be near-peer teachers are in line with those of previous researchers (Khapre et al 2021;Nestel & Kidd 2003;Tai et al 2017). Students who volunteer for peerteaching initiatives are more likely to present with effective teaching skills than those who choose not to volunteer.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, students participating in NPT show increased 'motivation through relevance and willingness to take intellectual risks' (Callese et al 2019, p. 3). Some authors claim that these advantages of NPT outweigh having topic experts as teachers (Burgess, McGregor & Mellis 2014;Taylor et al 2013), and there is growing evidence that the sensible use of peer teachers does not negatively impact academic achievements and learning (Bene & Bergrus 2014;Burgess et al 2014;Khapre et al 2021;.…”
Section: Theme 1 Near-peer Teaching Introductionmentioning
confidence: 99%
“…The near-peer teaching model establishes an educational relationship between learners and lecturers of similar learner level in which the lecturers are more advanced within the eld of interest than the learners. 13 Near-peer teaching improves learner satisfaction and knowledge acquisition and has been shown to lead to superior ECG interpretation skills when compared to self-directed learning. 14,15 Near-peers often have a better understanding of learners' meta-cognitive needs, which may explain the effectiveness of near-peer teaching models.…”
Section: Introductionmentioning
confidence: 99%